Differentiating Normal Myelination from Hypoxic-Ischemic Encephalopathy on T1-Weighted MR Images: A New Approach - Liauw, L. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Hypoxic-ischemic cerebral changes can be difficult to distinguish from normal myelination on T1-weighted images. We hypothesized that comparing signal intensity (SI) of brain structures on T1-weighted images enables differentiation of myelination from hypoxic-ischemic brain damage. MATERIALS AND METHODS: T1-weighted images, obtained in 57 infants aged 1–104 days and born after a gestational age of 35 weeks or older, were retrospectively evaluated. Subjects were assigned to a patient (n = 23, with perinatal hypoxic-ischemic encephalopathy [HIE] stage 2/3) or a control group (n = 34). In each subject, an SI score was assigned to 19 brain structures on the basis of pairwise comparisons with the other 18 structures. In both groups, mean total SI scores were calculated for the 19 structures. Independent samples t tests assessed whether the mean total score of a structure differed significantly between the 2 groups. Logistic regression assessed which comparison was best to distinguish between the groups and to predict the presence of hypoxic-ischemic injury. RESULTS: In patients, mean total SI scores for posterolateral putamen (PP) and peri-Rolandic cortex (PC) were significantly higher (P = .000 for both). Mean total SI scores of the posterior limb of internal capsule (PLIC) and the corona radiata (CR) were significantly lower in patients (P = .000 and 0.005, respectively). Two comparisons (PLIC versus CR, PP versus PC) were best to distinguish patients and controls and to predict absence or presence of HIE (P < .0001). CONCLUSION: SI changes due to hypoxia-ischemia can be differentiated from normal myelination by comparing SI of 4 brain structures on T1-weighted images.